Knowledge and Perceptions of Coastal Adolescents on TB and HIV/AIDS - Hikmawati Hikmawati; Sitti Muhsina; Srikandi Puspa Amandaty (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Knowledge and perceptions of adolescents in coastal areas about tuberculosis (TB) and HIV/AIDS have a significant impact on efforts to prevent and control these diseases. This study aims to examine the knowledge and perception of adolescents in coastal areas on TB and HIV/AIDS and the factors that influence their understanding. The design used in this study is quantitative with Cross Sectional approach method. The sample in this study was 32 adolescents using sampling techniques using Random Sampling. The results showed that adolescent knowledge about TB and HIV/AIDS tends to be limited. The majority of adolescents have a lack of in-depth understanding of the causes, symptoms, and ways of transmission of the two diseases. In addition, adolescents' perceptions of TB and HIV/AIDS are also influenced by cultural, social, and economic factors in their environment. The conclusion of this study is the need to improve education and information about TB and HIV/AIDS to adolescents in coastal areas. Approaches that involve local communities and pay attention to socio-cultural contexts are key in increasing adolescent understanding and awareness of both diseases. Thus, it is hoped that efforts to prevent and control TB and HIV / AIDS among adolescents can be more effective and sustainable.